Analisis Kemampuan Komunikasi Matematis Siswa Kelas VIII MTS Dalam Pembelajaran Matematika - Azha Apriliani; Depriwana Rahmi; Suci Yuniati; Annisah Kurniati (Jurnal Kajian Penelitian Pendidikan dan Kebudayaan, 2024)
The research was conducted to determine students' mathematical communication skills and their influence on mathematics education, consisting of 3 questions about number patterns. The instrument has gone through question validation, then given to class VIII students at one of the Pekanbaru MTS with procedures including: 1). Planning, 2). Implement, and 3). Assessing Results. The subjects in this research were 14 eighth grade students from the MTS Pekanbaru school. The approach to this research is descriptive and quantitative, and uses data collection techniques such as observation, data collected from test instruments, and errors in completion. The student's communication skills are in the "medium" category as shown by the research results.